Plastic waste management strategies toward zero waste: Status, perspectives and recommendations for Ethiopia - Tadele Assefa Aragaw (Cambridge Prisms: Plastics)
Since 1979, plastic companies have significantly expanded their markets. Evidence suggests that excessive plastic use in Ethiopia has exacerbated environmental pollution, contributing to a “quadruple crisis” involving climate change, biodiversity loss, pollution and public health and economic impacts. To address this, the Ethiopian government needs to establish effective plastic waste management strategies. Key future direction and recommendation include (1) Developing and enforcing national strategies, including a ban on many single-use plastics, for sustainable plastic waste management; (2) adopting international best practices and policies to move toward a zero-waste approach; (3) investing in a circular economy and plastic waste management systems; (4) strengthening policies through comprehensive legislation and extended producer responsibility frameworks; (5) establishing a council to integrate scientific research into policymaking; (6) promoting green technologies and innovations, such as plastic waste-to-energy and smart waste management; (7) engaging in global efforts to monitor hazardous chemicals in plastics and support transparency in a toxic-free circular economy to ensure the public’s right to information.